Quality of evidence of anti-obesity pharmacotherapy: an overview of systematic reviews - Rosa Camila Lucchetta; Bruno Salgado Riveros; Roberto Pontarolo; Rosana Bento Radominski; Fernando Fernandez-Llimós; Cassyano Januário Correr (São Paulo State University (UNESP), 2020)
The safety and effectiveness of main anti-obesity drugs are controversial, and there is no consensus among regulatory agencies regarding anti-obesity drugs. We undertook an overview of systematic reviews (SR) of randomized controlled trials (RCT) to summarize the quality of evidence related to anti-obesity drugs. Data sources included Medline, Scopus, The Cochrane Library and PROSPERO. Twenty-one SR (564 RCT; average of 2,356 participants per review) satisfied the inclusion criteria. Ten SR presented a high level of heterogeneity, and only five SR included sensitivity analyses. The most important limitations reported by the SR were a high level of attrition, a small sample size, and a short follow-up. Eight different outcomes for efficacy were used, 15 different outcomes for biomarkers were used, and nine different outcomes for safety were used. Conclusions: In conclusion, the quality of SR pertaining to anti-obesity drugs is low, and these reviews have a high level of heterogeneity. Future SR should present more detailed population inclusion criteria, larger sample sizes, and focus variables reported in a predefined anti-obesity core outcome set.